DESIGN OF MANAGEMENT AND PROMOTION IN THE DIGITAL APPLICATION BASED ON THE PT TEGUH CITA MADANI WEBSITE - Ahmad Farhan Habibi; Fahmi Kurniawan (Bahasa Indonesia, 2026)
The development of information technology encourages companies to adopt digital systems that can effectively support management and promotional activities. PT Teguh Cita Madani requires an integrated website-based system to manage company information and optimally deliver promotional content to the public. The main problem faced is the unavailability of digital media capable of integrating data management and promotional functions in a single, structured and easily accessible system. This study aims to design and build a website-based management and promotional system as a solution to this problem. The research method used is information system design research with a qualitative descriptive approach and is included in the Research and Development (R&D) category. The system development method uses the Waterfall model which includes the stages of needs analysis, system design, implementation, testing, and evaluation. The system was developed using HTML, CSS, JavaScript, PHP 8.1 technology, and the CodeIgniter 4 framework with a Model–View–Controller (MVC) architecture. The use of these technologies aims to produce a system that is structured, efficient, easy to develop, and in accordance with user needs. The results of the study indicate that the developed system is able to support data management and the delivery of company promotional information in an integrated manner. The system makes it easier for administrators to manage information and promotional content, and provides easy access to information for users. Based on testing and evaluation results, the system has performed according to the company's needs and has increased the effectiveness of information management and digital promotion. Therefore, the system can be used as an effective and sustainable website-based management and promotion tool.